Стратегії інтеграції освітньої та наукової діяльності університету: аналіз зарубіжного досвіду - Сбруєва, Аліна (Studies in Comparative Education, 2015)
У статті подано характеристику стратегій інтеграції освітньої та наукової діяльності університетів розвинених країн у процесі підготовки фахівців. Окреслено організаційні підходи до дослідно-орієнтованого навчання студентів. З’ясовано стратегії розв’язання досліджуваної проблеми у контексті визначення університетами своєї місії, розвитку курикулярних та методичних засад навчального процесу, розвитку наукової діяльності вишу, професійного розвитку персоналу. Класифіковано досліджувані стратегії відповідно до організаційних рівнів функціонування вишу. В статье дана характеристика стратегий интеграции образовательной и научной деятельности университетов развитых стран в процессе подготовки специалистов. Определены организационные подходы к исследовательско-ориентированному обучению студентов. Выяснены стратегии решения исследуемой проблемы в контексте определения университетами своей миссии, развития курикулярных и методических основ учебного процесса, развития научной деятельности вуза, профессионального развития научно-педагогического персонала. Исследуемые стратегии классифицированы в соответствии с организационными уровнями функционирования вуза. The characteristic of the strategies of educational and research activities integration of the universities in the process of specialist training has been given in the article. The topicality of the investigated problem in the context of demands to the University graduator, given in the European Qualifications Framework (EQF) and formulated in the Dublin descriptor of EQF, has been justified. Organizing approaches to the research-oriented studying of the students have been outlined. The system of the research culture values, forming of which is a vital element of the future teacher professional education under conditions of the knowledge society has been detailed. The importance of the theory and methodology of teaching in a higher school as a factor of the qualitative professional education has been shown. The strategies of solving the investigated problem according to the higher educational institution definition of their mission and its full understanding, development of the research-oriented curriculum and methodological principles; development of the strategies of the scientific activity in the specialist training; professional development of the staff aimed at formation of readiness to the research-oriented studying, and at modernization of the university organizing structures, capable of realizing of the university mission in the investigated sphere have been shown. The conclusion about strategies of integration of educational and scientific activity of the university as a complete system of interrelated and interdependent components having multilevel character has been drawn. The levels of such strategies and their subjects are the following: general institutional level (university), subinstitutional (educational and scientific structural subdivision of the university), department level (department), individual level (teacher, researcher). The strategies of educational and research activities integration of the universities in the advanced countries according to the organizing levels of their functioning have been classified into: institutional (political, administrative, scientific and pedagogical), subinstitutional (administrative, organizing methodological), department level (scientific methodological), individual level (scientific, methodological, organizing, pedagogical).